69th IFLA Congress in Berlin Management and Marketing of Libraries - Župan, Vesna (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
Lise Bissonnette gave the example of the construction of new library in Canada which would have characteristics of a municipal and national library.